Faktor-Faktor Yang Memperngaruhi Implementasi Kebijakan Perlindungan Pekerja Migran Indonesia di Jawa Timur - Prabowo, Andrew Patric (Journal of Governance and Administrative Reform, 2020)
Abstract This study aims to explain the factors that influence the success of the implementation of the Policy on the Protection of Indonesian Migrant Workers by the Department of Manpower and Transmigration in East Java with the George C. Edward III approach. This is important considering the need for special attention to PMI who are affected by problems during the pre-placement and post-placement processes. The method used in this research is descriptive qualitative research method. The selection of informants was done by purposive sampling. Data obtained through interviews, observation and documentation. The data analysis technique used qualitative analysis. The results of the research are aspects of good communication and coordination between the Manpower and Transmigration Offices and the UPT who are technically in charge of providing services related to the problems experienced by PMI. Factors that influence the successful implementation of policies to protect Indonesian migrant workers include: (a) Communication between stakeholders; (b) Resources; (c) Disposition; (d) Bureaucratic Structure. Keywords: Indonesian migrant workers, migrant worker policies Abstrak Penelitian ini bertujuan untuk menjelaskan faktor-faktor yang mempengaruhi keberhasilan implementasi kebijakan perlindungan pekerja migran Indonesia oleh Dinas Tenaga Kerja dan Transmigrasi Jawa Timur dengan pendekatan George C. Edward III. Hal ini penting mengingat perlu adanya perhatian khusus kepada PMI yang terkena masalah saat proses pra penempatan dan paska penempatan. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif deskriptif. Pemilihan informan dilakukan dengan purposive sampling. Data didapatkan melalui wawancara, observasi dan dokumentasi. Teknik analisis data menggunakan analisis kualitatif. Hasil penelitian adalah aspek komunikasi dan koordinasi yang baik antara Disnakertrans dan UPT yang bertugas secara teknis dibawanya dalam penyediakan pelayanan terkait permasalahan yang dialami oleh PMI. Faktor-faktor yang mempengaruhi keberhasilan implementasi kebijakan perlindungan pekerja migran indonesia diantaranya: (a) Komunikasi antar stakeholder; (b) Sumber Daya; (c) Disposisi; (d) Struktur Birokrasi. Kata kunci: pekerja migran Indonesia, kebijakan pekerja migran